DEVELOPMENT OF SCHOOLCHILDREN'S COMPETENCE TESTING TOOLS (Pedagogy of Higher and Secondary Education, 2004)
The author defines the notion of competence and analyses ways of developing student's competence. The advantages of test teaching technologies are examined.